2010
DOI: 10.1021/bm101054q
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying Osteogenic Cell Degradation of Silk Biomaterials

Abstract: The degradation of silk protein films by human mesenchymal stem cells (hMSCs), osteoblasts and osteoclasts, cells involved in osteogenic functions in normal and diseased bone, was assessed in vitro. The involvement of specific matrix metalloproteinases (MMPs) and integrin signaling in the degradation process was determined. Scanning electron microscopy (SEM) and atomic force microscopy (AFM) were used to quantitatively compare degradation by the different cell types using surface patterned silk films. Osteobla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
53
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 56 publications
(55 citation statements)
references
References 44 publications
1
53
0
Order By: Relevance
“…Shang et al [25] found the membranous materials prepared with regenerated silk fibroin containing low amounts (17-18%) of ß-sheets were easily degraded in water after pretreatment with proteinase XIV and co-culturing with fibroblasts (human corneal fibroblasts). These conclusions are in agreement with our findings, because regenerated silk fibroin [4][5][6][7][8][9][10][11][12]14,15,19,20,25] has a different inner structure and degradation properties to that of natural silk fibroin. Furthermore, serum contains a variety of enzymes that play synergic and antagonist actions.…”
Section: In Vitro and In Vivo Degradation Of The Silk And Degradationsupporting
confidence: 93%
See 4 more Smart Citations
“…Shang et al [25] found the membranous materials prepared with regenerated silk fibroin containing low amounts (17-18%) of ß-sheets were easily degraded in water after pretreatment with proteinase XIV and co-culturing with fibroblasts (human corneal fibroblasts). These conclusions are in agreement with our findings, because regenerated silk fibroin [4][5][6][7][8][9][10][11][12]14,15,19,20,25] has a different inner structure and degradation properties to that of natural silk fibroin. Furthermore, serum contains a variety of enzymes that play synergic and antagonist actions.…”
Section: In Vitro and In Vivo Degradation Of The Silk And Degradationsupporting
confidence: 93%
“…Pritcharda et al [10] prepared a sustained release system using regenerated silk fibroin, and investigated the effect of EDTA on inhibiting its degradation in the presence of proteinase XIV, thereby regulating its drug-release rate. Sengupta et al [20] explored the effect of steogenic cells on matrix metalloproteinases and the integrin signaling pathway in an in vitro degradation process of regenerated silk fibroin. Shang et al [25] found the membranous materials prepared with regenerated silk fibroin containing low amounts (17-18%) of ß-sheets were easily degraded in water after pretreatment with proteinase XIV and co-culturing with fibroblasts (human corneal fibroblasts).…”
Section: In Vitro and In Vivo Degradation Of The Silk And Degradationmentioning
confidence: 99%
See 3 more Smart Citations